Relaciones familiares y cogniciones románticas en la adolescencia: el papel mediador de la autoeficacia romántica. - Fernando Barrera**; Elvia Vargas *** (Revista de Estudios Sociales, 2005)
A conceptual proposal was examined concerning the influence of family relations on romantic autonomy and connectedness expectations in adolescents. Self-efficacy for romantic relations was construed as a mediating variable between perceived family relations and adolescents’ romantic expectations. Self-report measures of family and romantic cognitions were obtained form 326 female and male adolescents. Results showed that family relationships had direct effects on both selfefficacy and romantic expectations. A mediating significant effect of self-efficacy was established. These results are congruent with the social cognitive theory as well as the socialization theory.